Integrating DNA Methylation and Gene Expression Data in the Development of the Soybean-Bradyrhizobium N2-Fixing Symbiosis - Davis-Richardson, Austin G.; Russell, Jordan T.; Dias, Raquel; McKinlay, Andrew J.; Canepa, Ronald; Fagen, Jennie R.; Rusoff, Kristin T.; Drew, Jennifer C.; Kolaczkowski, Bryan; Emerich, David W.; Triplett, Eric W. (Frontiers in Microbiology, 2016)
Eukaryote-bacteria symbioses are common in nature and several have been extensively studied. However, very little is known about the role of epigenetics in the differentiation of a bacterium from the free-living to the symbiotic state. Here the first genome-wide analysis of DNA methylation changes between these states is described using the model of symbiosis between soybean (Glycine max (L.) Merr.) and its root nodule-forming, nitrogen-fixing symbiont, Bradyrhizobium diazoefficiens. Resequencing the genome of B. diazoefficiens from both states using the Pacific Biosciences sequencing platform revealed 43,061 sites representing five motifs with the potential to be methylated in the 9.2 Mb genome. Of those sites, 3,276 changed methylation states in 2,921 genes or 35.5% of all genes in the genome. Over ten percent (10.9%) of the methylation changes occurred in the 681-kb sized symbiosis island that comprises just 7.4% of the genome. The CCTTGAG motif was methylated only during symbiosis with 1,361 adenosines methylated among the 1,700 possible sites. Published microarray data was used to correlate the methylation status with gene expression. Another 89 genes within the symbiotic island and 768 genes throughout the genome were found to have methylation and significant expression changes during symbiotic development. Of those, nine known symbiosis genes involved in all phases of symbiotic development including early infection events, nodule development, and nitrogenase production. These associations between methylation and expression changes in many B. diazoefficiens genes suggest an important role of the epigenome in bacterial differentiation to the symbiotic state.